2018
DOI: 10.1021/acs.chemmater.7b04800
|View full text |Cite
|
Sign up to set email alerts
|

Biotemplated Lightweight γ-Alumina Aerogels

Abstract: We present the biotemplating of γ-Al 2 O 3 aerogels with chitosan nanofibrils. Aluminum−chitosan interactions cause the swelling of iridescent chitosan structures into helicoidal hydrogels and the subsequent aqueous dissolution of swollen fibrils to form Al− chitosan solutions. Viscous aqueous solutions of Al 3+ −chitosan hybrid nanofibers were freeze-dried to give lightweight cotton-like aerogels. Homogeneous incorporation of Al 3+ ions into chitosan yields water-soluble nanofibrils that can serve as polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…The meso-and macroscale pores may be formed by the agglomeration of NiO nanoparticles 34 and assembly of the nanoplates. 8 The novel porous NiO nanostructures usually give rise to the unique gas sensing properties originating from the defective sites on their surface. The gas sensing behavior of the as fabricated mesoporous NiO nanoplates was tested with H 2 S, NH 3 , CO and H 2 gases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meso-and macroscale pores may be formed by the agglomeration of NiO nanoparticles 34 and assembly of the nanoplates. 8 The novel porous NiO nanostructures usually give rise to the unique gas sensing properties originating from the defective sites on their surface. The gas sensing behavior of the as fabricated mesoporous NiO nanoplates was tested with H 2 S, NH 3 , CO and H 2 gases.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al 7 reported the successful fabrication of mesoporous TiO 2 with high exposure of the (001) faces using a cellulose nanocrystal template. Nguyen et al 8 successfully converted hierarchical chitosan nanobril templates into lightweight g-Al 2 O 3 aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the emulsion template method, a bio-template method has been developed by MacLachlan's group for the fabrication of light-weight alumina nanofiber aerogels. 65 In this method, the biomaterial chitosan nanofibrils as templates were mixed with Al 3+ aqueous solution to produce Alchitosan hydrogels that can be converted to an aerogel by freeze-drying. Thermal decomposition of the composite aero-gels yielded Al 2 O 3 aerogels that possessed similar structural organization as that of the chitosan nanofibril aerogels.…”
Section: Template-based Gelationmentioning
confidence: 99%
“…Việc sử dụng polymer tự nhiên làm chất định hướng cấu trúc để tổng hợp các vật liệu nhẹ và có độ xốp cao rất được quan tâm vì loại polymer này thân thiện với môi trường, phong phú, có cấu trúc độc đáo và chi phí điều chế thấp [6]. Các polymer sinh học như peptide [7], dextran [8], xyloglucan [6], cellulose [9], chitin [10] và chitosan [11]…”
Section: Mở đầUunclassified